International labor migration as a strategy of economic stabilization at the household level in Mexico and Central America - ZÁRATE-HOYOS, Germán (Papeles de Población, 2008)
This paper looks at international migration and remittances as a strategy of economic stabilization. It examines the stability of these flows at the macro level and questions the stability and the actual flows in the official statistics. Controversy still exists between academics, bank officials and multilateral organizations about the true size of these flows. Mexico is a good case study because it is the largest recipients of remittances in Latin America and it has one of the best accounting methods. Yet, questions remain about official flows and the lack of a clear methodology for capturing collective remittances and even social remittances. It is also important to understand that the failure of neo-liberal policies to spur sustained economic growth and employment is in turn a cause of increased migration and consequently increased remittances. The relationship between migration and neo-liberal policies must be closely examined before turning to remittances as a panacea for development.